"Land Grabbing" in an Autocracy and a Multi-Party Democracy: China and India Compared. Issue 3 (26th May 2020) - Ong, Lynette H.
ABSTRACT: Both China and India have witnessed extensive land expropriation by the state from farmers for use in industrialisation and urbanisation projects. Land conflicts have ensued from these developments. This article poses two questions: (i) Why do we see a similar escalation of land dispossession in both countries, despite their distinctively dissimilar political systems, one being a one-party authoritarian regime, the other being a multi-party democracy?; and (ii) How does the different regime type affect the politics of dispossession? Despite their diverse political institutions, government officials have been given similar incentives to chase growth by developing land, but the institutions create diverging environments for aggrieved citizens to mobilise for collective action. While it is unsurprising that the interests of the poor and weak are not protected in an autocracy, democracy provides no automatic safety valve in defending marginalised citizens either.